Smoking-related interstitial fibrosis (SRIF): pathologic findings and distinction from other chronic fibrosing lung diseases. Issue 10 (27th April 2013) - Katzenstein, Anna-Luise A
Abstract : Smoking-related interstitial fibrosis (SRIF) is a common, histologically striking finding in smokers that must be distinguished from the idiopathic interstitial pneumonias and other chronic interstitial fibrosing lesions. It is characterised by marked thickening of alveolar septa by fibrosis composed of thick collagen bundles that have a distinctive hyalinised quality and often are admixed with variable numbers of hyperplastic smooth muscle fibres. There is minimal accompanying inflammation. This fibrosis is usually most prominent in subpleural and centrilobular parenchyma, but can be present elsewhere as well. It is accompanied by emphysema and respiratory bronchiolitis. Most patients are asymptomatic or only mildly symptomatic, and the clinical course is stable in most. This paper reviews the pathologic features of SRIF in detail, its differentiation from more ominous interstitial fibrosing processes, and the clinical implications of its diagnosis.